Effect of Music Therapy on Sleep Quality in Older Persons - ณ วิเชียร สุรีรัตน์; จินตนาวัฒน์ โรจนี; กล้าผจญ จักรกริช; นานาศิลป์ ภารดี (Journal of Thailand Nursing and Midwifery Council, 2018)
Objective: To examine how music therapy could beneft older adults’ sleep quality. Design: Quasi-experimental research. Procedure: Fifty-two participants were recruited according to the inclusion criteria and equally assigned to the experimental and control groups (26 persons in each group). The participants were older adults with poor sleep quality, living in Phitsanulok City’s municipal area. The experimental group received one music therapy session (30-45 minutes) per day before bedtime, at least three days a week, for four consecutive weeks. The control group, on the other hand, did not receive any music therapy. The instrument used for assessing sleep quality was the Pittsburgh Sleep Quality Index (PSQI). Data were analysed using descriptive statistics, independent t-test, and paired t-test. Results: After receiving music therapy, the experimental group’s sleep quality was signifcantly better that that of the control group (p < .001). In addition, the experimental group displayed signifcantly higher sleep quality than before they received music therapy (p < .001). Recommendations: The fndings of this study indicate that music therapy can improve sleep quality among older adults.